Fermentation of Molasses by Clostridium spp. for Biohydrogen and Biomass Production: A Step Toward Renewable Energy and Circular Bioeconomy (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Molasses, a carbohydrate-rich by-product of the sugar industry, it presents an abundant and low-cost substrate for microbial cultivation. This study evaluates the potential of molasses for biohydrogen (H₂) and biomass production using pure cultures of four obligate anaerobic Clostridium species: C. pasteurianum DSM525, C. beijerinckii DSM791, C. acetobutylicum DSM792, and C. intestinale DSM6191. Batch fermentations were performed at 4%, 8%, and 10% (w/v) molasses concentrations within an initial pH range of 6.0. Throughout a 168-hour incubation period, microbial growth and metabolic performance were assessed by monitoring optical density at 600nm (OD₆₀₀), pH fluctuations, oxidation-reduction potential (ORP), gas-phase hydrogen production, ethanol accumulation, total carbohydrate (TC) consumption, and volatile solids (VSs) reduction. Notably, all strains exhibited robust fermentative activity, with the efficient biomass and hydrogen yields recorded at 4% and 8% substrate concentrations. Maximal microbial biomass was achieved with OD₆₀₀ values up to 1.6, indicating efficient carbon utilization and cell density increase. Among the strains, C. beijerinckii demonstrated the most promising biohydrogen output, producing up to 1093 ± 10 ml L-1 H₂, alongside measurable ethanol production and substantial carbohydrate degradation. A marked decline in ORP (as low as -508 ± 10 mV) corresponded with increased hydrogen output, underscoring the strong anaerobic nature of these metabolic pathways. Carbohydrate removal efficiencies varied by species, reflecting diverse metabolic strategies and fermentation profiles across the tested Clostridium spp. The simultaneous generation of biohydrogen and biomass signifies a dual valorization pathway for molasses, with implications for both clean energy and microbial-based bio-products. This research highlights raw molasses as a promising low-cost substrate for integrated biohydrogen and biomass production, advancing sustainable waste-to-energy technologies. The application of Clostridium spp. in bioconversion processes demonstrates a viable route for agro-industrial residue utilization, reinforcing the circular bioeconomy model and contributing to green energy development․
Keywords: Clostridium spp; biohydrogen; molasses fermentation; anaerobic digestion; circular bioeconomy; microbial biomass